2004
DOI: 10.1074/jbc.m313581200
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Disease-associated Mutations on the Folding Pathway of Human Prion Protein

Abstract: Propagation of transmissible spongiform encephalopathies is believed to involve the conversion of cellular prion protein, PrP C , into a misfolded oligomeric form, PrPSc . An important step toward understanding the mechanism of this conversion is to elucidate the folding pathway(s) of the prion protein. We reported recently (Apetri, A. C., and Surewicz, W. K. (2002) J. Biol. Chem. 277, 44589 -44592) that the folding of wild-type prion protein can best be described by a three-state sequential model involving a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
137
3
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(154 citation statements)
references
References 58 publications
13
137
3
1
Order By: Relevance
“…Previous kinetic studies of PrP folding have shown that at low temperature (5°C), the human protein folds by way of a populated intermediate (14)(15)(16). The rate-limiting conversion of this species into the native state occurs at Ϸ1,400 s Ϫ1 , some 14-fold slower than the rate-limiting step at 25°C measured in our current study.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…Previous kinetic studies of PrP folding have shown that at low temperature (5°C), the human protein folds by way of a populated intermediate (14)(15)(16). The rate-limiting conversion of this species into the native state occurs at Ϸ1,400 s Ϫ1 , some 14-fold slower than the rate-limiting step at 25°C measured in our current study.…”
Section: Discussioncontrasting
confidence: 39%
“…Because we cannot perform perturbation experiments at low denaturant concentrations, it is not possible to detect the presence of such an unstable intermediate by using our higher-temperature data. A major objective of the work of Surewicz and colleagues was to investigate the effects of naturally occurring mutations in PrP that lead to inherited prion disease (15). The broad conclusion was that 2/3 of these stabilized the intermediate, but folding rates were essentially the same.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the vast majority of point mutations associated with these disorders map to the region found herein to undergo a transition to ␤-structure (4). Thus, these mutations are well positioned to cause structural and/or thermodynamic perturbation of this critical region in PrP C (40), thereby facilitating the spontaneous conversion to the PrP Sc isoform. The present structural model may also offer a rationale for baffling findings that the pattern of glycosylation (i.e., the ratio of diglycosylated, monoglycosylated, and unglycosylated PrP) is one of the determinants of prion strain diversity, being fatefully propagated upon transmission (2,4).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments on mouse PrP mutants indicate that thermodynamic stability of PrP is significantly reduced for T183A and F198S and somewhat reduced for V180I [136]. For V180I, V210 and F198S PrP, it was found that a folding intermediate increased in the population relative to the native fold, further indicating that these mutations cause instability [89,151]. Studies of V203I PrP are limited, but may suggest an effect on stability as well [152].…”
Section: Mutations In the Hydrophobic Corementioning
confidence: 99%